PENERAPAN ASAS AUDI ET ALTERAM PARTEM PADA PERKARA WANPRESTASI DALAM HAL KETIDAKHADIRAN PIHAK TERGUGAT DI PENGADILAN NEGERI PEKANBARU - Desi Bangun; Evi Deliana; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the civil procedural law the judge must listen to both parties (Audi Et Alteram Partem) based on Article 4 paragraph (1) of Law Number 48 Year 2009 concerning Judicial Power. However, in practice the application of this principle has not been well implemented, due to the absence of the defendant in the trial process. Based on this fact, there are 3 problem statements in the writing of this thesis, namely: First How is the application of the Audi Et Alteram Partem principle in the Default Case in the absence of the defendant in the Pekanbaru district court decision? Second How is the resolution of the Audi Et Alteram Partem principle in the Default Case in the absence of the defendant in the Pekanbaru District Court? and the obstacles faced by the Pekanbaru District Court judges in applying the principle of Audi Et Alteram Partem to the Default Case in the absence of the defendant?This type of research is sociological research, because this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. The study was conducted at the Pekanbaru District Court, while the population and sample were all parties concerned with the problem under study, the data sources used were primary data, secondary data, and tertiary data, the data collection techniques in this study were interviews and literature review.From the results of this study have 3 main things that can be concluded. First. The application of the Audi Et Alteram Partem principle has not gone well in the Pekanbaru District Court. Second, the settlement of the case for default in the absence of the defendant. Third, the obstacle faced by the judge is the inactivity of the defendant to attend the trial process.Keywords: Application-principle-Audi Et Alteram Partem-Absenteeism